A new species of Chrysobothris Eschscholtz from Oregon and Washington, with notes on other Buprestidae (Coleoptera) occurring in the United States and Canada - Westcott, Richard L. (Zootaxa, 2005)
Chrysobothris eriogoni Westcott, new species (Buprestidae), from Oregon and Washington is described and figured. New synonymy is presented under Acmaeodera haemorrhoa LeConte (=A. bouvieri Kerremans) and A. solitaria Kerremans (=A. thoracica Kerremans). Biological, distributional and taxonomic notes are presented for 43 other species in the following genera: Acmaeodera, Acmaeoderoides, Acmaeoderopsis, Agrilus, Anambodera, Anthaxia, Brachys, Buprestis, Chrysobothris, Dicerca, Paratyndaris, Poecilonota, Spectralia.